AKTIVITAS ANTIOKSIDAN EKSTRAK DIKHLOROMETANA DAN AIR JAHE (Zingiber officinale Roscoe) PADA ASAM LINOLEAT [Antioxidant Activity of Ginger (Zingiber officinale Roscoe) Dichloromethane and Water Exctract on Linoleic Acid] - Aisyah Tri Septiana; Deddy Muchtadi; Fransiska R. Zakaria (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
Antioxidant activity of various ginger extracts are different. The aims of this work are to determine the antioxidant activity of ginger extracts on linoleic acid. The antioxidant activities were tested on linoleic acid supplemented with water and dichloromethane extract of ginger. The antioxidant activity was tested by measuring malonaldehide absorbance. Total phenol and iron content of the extracts were analyzed by spectrometry. This research showed that antioxidant activity of water and dichloromethane extract of ginger was stronger than a-tocopherol, and antioxidant activity of dichloromethane extract is stronger than water extract of ginger. Antioxidant activity of ginger extracts, seems to be correlated with the total phenol and iron contents.